80/20 Rule : How to Use it for Effective Business - Anitha, T.; Lenin Kumar, Nooney (Indian Journal of Marketing, 2008)
Any individual business can gain immensely through practical application of Pareto’s Principle.This rule states that in many aspects of business and life, 80% of the potential value can be achieved from just 20% of the effort, and that one can spend the remaining 80% of effort for relatively little return. The key theme of the 80/20 Principle applied to business is how to create the greatest stakeholder value and generate most money with the least expenditure of assets and efforts. The most important use of the 80/20 Principle is "to isolate where the company is really making the profits and, just as important, where company is loosing money". The reverse is true too, that things that take up 80% of time and resources will only produce 20% of results. It has been said that the 80/20 rule exists in every field, ranging from business to people. We can apply the 80/20 Rule to almost anything, from the science of management to the physical world. The present article focuses on how companies can achieve progress by applying this principle and also examines the top 10 Pareto’s principles that can be applied for effective business.